Cover Feature: Conformer Distribution in Rotaxanes Containing Nonsymmetric Threads: A Systematic Approach (Eur. J. Org. Chem. 36/2018). Issue 36 (3rd September 2018) - Orlando, Tainára; Salbego, Paulo R. S.; Zimmer, Geórgia C.; Pagliari, Anderson B.; Bender, Caroline R.; Rodrigues, Leticia V.; Bonacorso, Helio G.; Zanatta, Nilo; Berná, Jose; Martins, Marcos A. P.
Abstract : The Cover Feature shows the threads and rotaxanes, the actors in the play "Conformer Distribution". The plot will present the story of how the conformers distribution changes when the threads are involved by the macrocycle in the rotaxane formation. The theater acts will present different approaches in the solution, solid state and crystal. After the various acts, the audience will be lead to the climax story and the final resolution. The Rectory of the UFSM is kindly acknowledged for the theater picture image. More information can be found in theFull Paper by M. A. P. Martins et al.